Analisis Penggunaan Model Problem Based Learning dalam Kemampuan Berpikir Kritis Siswa SD - Ulfiatur Rosyidah; Ismail Marzuki (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The problem based learning model is a learning process that allows students to become open, reflective, active, reflective and critical thinkers through activities related to real world situations. The aim of this research is to analyze the application of the problem based learning (PBL) method to improve elementary school students' critical thinking abilities, and the PBL model is a problem-based model that can improve students' thinking abilities. This research uses a systematic literature review. In this method, there are 5 stages carried out in this systematic literature review. The stages of this research are problem identification, literature search, literature selection using 1 RQ, and finally reporting the results. This research was conducted on scientific articles from 2016 to 2024. Researchers used Google Scholar to search for samples and found 10 articles aimed at elementary school students. Researchers used quantitative comparative methods to analyze research results. Based on the results of the analysis, it shows that the problem-based learning model increases students' critical thinking abilities from a minimum of 25.60% to a maximum of 77.30%, resulting in a significant increase of 58.412%.